Concrete density estimation of linac bunker walls using impact-echo testing. (September 2020) - Trauernicht, Christoph Jan; Moosa, Farhana; Blassoples, Garth; Okwori, Emmanuel; Nyoni, Bukhosi Raphael; Moyo, Pilate; Burger, Hester
Highlights: A non-destructive method is described that can be used to confirm shielding integrity of a bunker. Impact-echo testing is done before the installation of the linear accelerator. This is a viable solution to check shielding integrity before linac installation. Abstract: Purpose: To estimate the concrete density of a newly constructed bunker using impact-echo testing prior to the installation of the linear accelerator. Methods: A newly constructed bunker showed visible honeycombing after the removal of the construction formwork. Impact-echo testing, which is based on the propagation and reflection of elastic waves in solids, was applied to confirm the bunker shielding integrity. A mechanical impact on the bunker wall generates a stress pulse, which propagates through the wall and is reflected or refracted by voids or changes in material characteristics such as density. Surface displacements caused by the reflected waves are recorded by a transducer, located near the impact point. The resulting displacement-time curves are analysed in the frequency domain for anomalies. The dominant frequencies are related to the depths from which stress waves are reflected within the structure. If the dynamic elastic modulus and Poisson ratio of the concrete are known, then the measured velocity of the so-called P-wave can be related to the concrete density. Results: Validation measurements on a wall with known concrete density gave an estimate within 3% of the true density. Measured velocities on the honeycombed wall ranged from 3750 m/s to 4300 m/s, corresponding to densities of 2894 kg/m 3 and 2201 kg/m 3 respectively, with the majority of estimated densities ranging from 2307 kg/m 3 to 2544 kg/m 3 . A radiation survey after the installation of the linear accelerator confirmed adequate shielding. Conclusion: Impact-echo testing presents a viable solution to confirm bunker shielding integrity before the installation of a linac.